The Japanese art - Stump, Cora Idell (My University, 1895)
Introduction: The Japanese art in all probability originated from the Chinese art. We should scarcely expect anything different. Japan is young in comparison with its neighboring country China, which has stood as a nation of artists almost since the beginning of history. But it is distinctly understood that art was greatly modified in passing from nation to nation and even while Japan was yet in its pupilage its national character was asserting itself. Its world wide renown lies in a people quick in perception, and possessing a marked imitative power and it is their own national genus that has raised the standard of their art. The origin of their art dates back as far as the tenth century, and in its infancy it was not without its many influences, Europe just then in its maturity, eastern Asia, China, all influenced it more or less, but it is the Japanese own individuality that people admire, and not a combination of the stern Greek with the Oriental. Japanese artists have such a keen perception of harmony which exists between the ornament and the subject for which it is to be used and it is recognized that the artistic beauty lies not in their drawings (the exact copy of things and objects as they are) but the harmonious color effect is paramount and its beauty obscures the incongruities of composition. The Japanese appear to have thoroughly grasped the true place of color in decoration of curving surfaces, patterns and colors are selected which the curvature makes stand out in all their beauty and delicacy. This people are not only masters of the clay for pottery, the marble for monuments and paper for dresses, but many substances which citizens of this country have never heard of or seen.
Citation: Stump, Cora Idell. The Japanese art. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Art; Japanese; Theses; Manuscripts (documents)